The Effect of Carbon Coatings on the Electrochemical Performance of Composite Electrodes. (24th April 2020) - Gonzalez, Gabriel; Gonzalez, Ramiro; Zuniga, Luis; Chipara, Mircea; Alcoutlabi, Mataz
Abstract : The present work focuses on the large-scale production of Fe2 O3 /C, TiO2 /C and Fe2 O3 /TiO2 /C composite fibers by centrifugal spinning (CF). Fe2 O3 /PVP, TiO2 /PVP, and Fe2 O3 /TiO2 /PVP precursor solutions were prepared and centrifugally spun at 7200 RPM to obtain precursor micro fibrous mats. The precursor fibers were then stabilized in air at 200 °C for 3 hours followed by calcination in Argon atmosphere at 500 °C for 4 hours to obtain composite carbon fibers. In addition, TiO2 -slurry based electrode was prepared from mixing 70% of TiO2 active material with 20 % carbon black and PAN binder. The TiO2 electrode delivered a good electrochemical performance and cyclability. The Fe2 O3 /C, TiO2 /C and Fe2 O3 /TiO2 /C composite-fiber anodes demonstrated a stable cycling performance with a discharge capacity of 200, 144, and 235 mAh g -1 respectively after 100 cycles at 100 mAh g -1 with the exception of the first cycle which was tested at 50 mAh g -1 . The high surface area of the centrifugally spun composite fibers resulted in high irreversible capacity at the first cycle compared the slurry-based electrode. Although these composite electrodes exhibited stable capacity and a decent cyclability, further work is required to improve the Coulombic efficiency of composite-fiber electrodes and enhance their overall electrochemical performance and rate capability.